Evaluation of Status of Feedback in Clinical Education from the Viewpoint of Nursing and Midwifery Professors and Students and Relevant Factors - Afsaneh Safaei Koochaksaraei; Masoomeh Imanipour; Mehrnaz Geranmayeh; Shima Haghani (Zanjan University of Medical Sciences and Health Services, 2019)
Volume 11, Issue 32 (3-2019) J Med Educ Dev 2019, 11(32): 43-53 | Back to browse issues page DOI: 10.29252/edcj.11.32.43 XML Persian Abstract Print Download citation: BibTeX | RIS | EndNote | Medlars | ProCite | Reference Manager | RefWorks Send citation to: Mendeley Zotero RefWorks Safaei Koochaksaraei A, Imanipour M, Geranmayeh M, Haghani S. Evaluation of Status of Feedback in Clinical Education from the Viewpoint of Nursing and Midwifery Professors and Students and Relevant Factors. J Med Educ Dev. 2019; 11 (32) :43-53 URL: http://zums.ac.ir/edujournal/article-1-1085-en.html Evaluation of Status of Feedback in Clinical Education from the Viewpoint of Nursing and Midwifery Professors and Students and Relevant Factors [Edit] [Profile] Afsaneh Safaei Koochaksaraei , Masoomeh Imanipour * , Mehrnaz Geranmayeh , Shima Haghani School of Nursing and Midwifery, Tehran University of Medical sciences,Tehran,Iran Abstract: (6098 Views) Background & Aim: The main goal of each educational system is successful implementation of the learning process. One of the tools used to achieve this goal is providing effective feedback to students during the learning process. Since clinical education forms majority of medical sciences education (e.g., nursing and midwifery), providing feedback to students during clinical education is of paramount importance. Therefore, this study aimed to evaluate the status of feedback provision in clinical education from the viewpoint of nursing and midwifery professors and students and to determine its relevant factors. Materials and Methods: This descriptive and analytical research was performed on all BSc nursing and midwifery students (third-semester upward) and all clinical professors in 2016-2017. In total, 198 students and 50 professors were enrolled in the study. Data were collected using a researcher-made questionnaire, validity, and reliability of which were confirmed using content and face validity and test-retest, respectively. In addition, data analysis was performed in SPSS using descriptive statistics and independent t-test. Results: In this study, 73.2% of students and 74% of professors considered the status of feedback provision in clinical education as moderate, and no significant difference was in the viewpoint of them in this regard (P=0.38). According to the results, the most used type of feedback was oral and individual feedback, and the most important cause of lack of provision of effective feedback included inadequate scientific mastery in the relevant subject, lack of knowledge and skill of professors regarding feedback provision principles, high number of students, and short duration of internship. Conclusion: Despite the impact of feedback on the effectiveness of education and improvement of the teaching-learning process, the present study demonstrated the status of feedback provision in clinical education is not desirable and different factors are related to this issue. Therefore, it is necessary to design some solutions to improve the abilities of professors in the areas of providing feedback and helping the improvement of clinical education.